Lipase-catalyzed production of pyridoxine monolaurate in solvent-free bioreactor system. (15th January 2023) - Yu, Hyunjong; Kim, Sungjun; Chang, Pahn-Shick
Highlights: Pyridoxine monolaurate was produced via Lipozyme 435-catalyzed esterification. Solvent-free gas bubbling system improved production of pyridoxine monolaurate. Volumetric productivity (41.24 mmol/L/h) and conversion (84.49 %) were achieved. Lipase reusability was higher in gas bubbling system than magnetic stirring systems. Pyridoxine monolaurate can be used as a nutritional emulsifier for beverages. Abstract: This study demonstrated that solvent-free gas bubbling system enhanced production efficiency of pyridoxine monolaurate in the esterification catalyzed by immobilized Candida antarctica lipase B (Lipozyme 435). Volumetric productivity in solvent-free gas bubbling system (41.24 mmol/L/h) was 3.7 and 2.1-fold higher than those in conventional organic solvent system (11.10 mmol/L/h) and solvent-free system (19.86 mmol/L/h) using magnetic stirring, respectively. Among the three bioreactor systems, solvent-free gas bubbling system provided the best reusability of the lipase retaining 94.45 % of initial activity for six batch reactions. In the bioreactor system, 5- O -lauroyl-pyridoxine was regioselectively produced with maximum production of 371.17 mmol/L at 70 °C and 0.10 of substrate molar ratio ([pyridoxine]/[lauric acid]) for 9 h. Pyridoxine monolaurate exhibited interfacial activity at oil-water interfaces, suggesting it had emulsifying properties. Pyridoxine monolaurate is expected to be applied as a multi-functional emulsifier with nutritional values to replace both small molecule emulsifiers and pyridoxine hydrochloride in fortified beverages.